CYTOTOXIC LABDANE DITERPENOIDS ISOLATED FROM THE HEXANE FRACTION OF THE Croton stipuliformis STEM BARK - FRANCO, Martha S.; CORDERO, Claudia P.; ARISTIZABAL, Fabio; OSORIO R., Coralia (Vitae, 2011)
The composition of the cytotoxic hexane fraction of the Croton stipuliformis bark was studied by means of a gas chromatography coupled to a mass spectrometry; sesquiterpenes and sterols were characterized as the main constituents. Along with these compounds, three labdane and seco-labdane diterpenoids, 8(17),12E,14-labdatrien-18-oic acid [3], 12E-3,4-seco-labda-4(18),8(17),12,14-tetraen-3-oic acid [2], and its methyl ester [1] were isolated from this fraction through preparative HPLC, and their structures were elucidated by HR-FABMS, 1D and 2D NMR analyses. Additionally, the cytotoxic activity of these three compounds against human tumor cell lines HEp-2, HT-29, MKN-45, MCF-7, and HeLa was assessed. The three compounds showed a non-specific and moderate cytotoxicity against the abovementioned cell lines.